Z. mauritiana Leaves as Larvasidal Alternatives (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
The development of resistance to chemical insecticides among mosquitos has been considered as a setback in vector control. However, the use of chemical insecticides is often toxic to both human and non-target animals, thus it needs the development of natural insecticides. This study aims to analyze the larvicidal effect of Z. mauritiana leaves as a natural larvicidal that is friendly to the environment. This research will outline the larvicidal effect of Z. mauritiana leaves and discuss the significance of addressing this natural larvicide against Aedes aegypti larvae. Methods and Material in this study, we developed a mosquito larvacide by extracting Z. mauritiana leaves with the maceration method. We extracted Z. mauritiana leaves into 5 different concentrations (1%, 3%, 5%, 7%, 9%) and its effect compared to the current chemical larvicide (1% of temephos). Data analysis was performed by using the computer and statistical of variance test One Way Anova. This experiment was successfully 100% killed Aedes aegypti in 24 hours of the intervention of 9% extract of Z. mauritiana leaves which was a powerful effect compare to recent studies. The intervention of concentration variations was significantly associated with larvae mortality (p ≤ 0,001).